Plan de marketing digital para una mayor captación de estudiantes en la Universidad Antonio Nariño Sede Santa Marta. (2020)
The main objective of this research was to design a digital marketing plan for the Universidad Antonio Nariño, Santa Marta headquarters, in order to generate a greater recruitment of students in the enrollment of the different careers offered by this University. The study was developed with the methodology of a case study, with a mixed and descriptive approach, developed through a field design, with the use of investigative techniques such as direct observation, the questionnaire and the documentary review, as well as for the collection From the information, investigative instruments such as the interview and the survey were applied, which were applied to a previously defined population and in a sample calculated using the formula of Lincoln Shao (1996) for statistically infinite populations, obtaining a total of 385 individuals. In the first moment of the development of the work, a diagnosis was made, in which an analysis of the internal conditions of the Antonio Nariño University, Santa Marta headquarters was carried out, in which it was necessary to apply an interview to a section of the university, likewise An analysis of the external environment was carried out, for which a survey was applied to a population that is considered a target market of the Antonio Nariño University, Santa Marta, then an inferential analysis of the information obtained in the application of said instruments and the Findings were decisive for the elaboration of the SWOT matrix, in order to know the current conditions Antonio Nariño University headquarters Santa Marta, both in its internal structure and in relation to the conditions with its environment. Finally, the digital marketing plan designed to obtain a greater recruitment of students for this institution is proposed and the conclusions and recommendations of the study are exposed.